PENGARUH KUALITAS PELAYANAN, DAN TARIF TERHADAP KEPUASAN WISATAWAN CIMORY ON THE VALLEY - Kharismawati, Ria; Ria Kharismawati; Febryantahanuji Febryantahanuji (LPPM Universitas Sains dan Teknologi Komputer, 2025)
This study aims to determine and analyze the direct effect of Service Quality on Tourist Satisfaction at Cimory on the Valley, to determine and analyze the direct effect of Tariff on Tourist Satisfaction at Cimory on the Valley, and to determine and analyze the simultaneous effect of Service Quality and Tariff on Tourist Satisfaction at Cimory on the Valley. This study uses a quantitative method with a sample of 80 Customer respondents. The data were analyzed using data analysis techniques of validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple regression analysis test, T test, F test, R2 determination coefficient test. The results of the study indicate that directly Service Quality has a significant effect on Tourist Satisfaction at Cimory on the Valley, directly Tariff has a significant effect on Tourist Satisfaction at Cimory on the Valley, and directly and simultaneously Service Quality and Tariff have a significant effect on Tourist Satisfaction at Cimory on the Valley.